Youths and risky sexual behaviour: a kap study on HIV/AIDS amongst University of Ibadan student (2009)
This study examined knowledge, awareness and attitude of sexual behaviour as factors likely to affect risk-taking behaviours. Six hundred undergraduates of the University of Ibadan participated in this cross-sectional survey (100 Level and 400 Level students). Data were collected using three structured and validated scales. Results indicated that HIV transmission knowledge has a significant effect on sexual risk-taking behaviours. Misconception on the transmission of HIV/AIDS was also been reported and had a significant effect on risk-taking behaviours. Inadequate and inappropriate knowledge of HIV increases youths' risky sexual behaviours. An attitude such as one cannot contract HIV in their first time of sexual intercourse also increases their chances of risky behaviour. It is, thus, recommended that HIV awareness campaigns be intensified, while attitude-change initiatives should be embarked upon to discourage youths from risky sexual behaviour.